PWE-010 Monitoring IBD Medications in Primary Care: Audit of Practice in South West London. (17th August 2016) - Alexakis, C; Oliver, C; Hockney, E; Amoyel, A; Grayson, C; Pollok, R; Saxena, S
Abstract : Introduction: IBD is increasing in the UK. Primary care will likely have a greater role in the management of such patients under 'shared-care' protocols, particularly with regards to drug monitoring and vaccination requirements. A recent national audit indicated varied prescribing practices amongst GPs treating patients with IBD. 1 To address local prescribing behaviours, we audited 4 practices in SW London, against established standards for IBD care. Methods: Patients with Crohn's disease (CD) or ulcerative colitis (UC) were identified retrospectively from the records of 4 practices in SW London. Information collected included the number of patients on 5 aminosalicylates (5 ASA) and azathioprine (AZA) for the previous year. The following audit standards were generated, derived from IBD guidelines; 2, 3 patients on 5 ASA require yearly renal function; 5 ASA should not be used in CD as maintenance therapy; prolonged (>3 months) or repeated steroid courses (>1/year) should be avoided; patients on AZA should have blood monitoring every 2–3 months; patients on AZA should be offered annual Pneumococcal and Influenza vaccination. Results: 70 patients with UC and 45 with CD were identified. 41% UC were on maintenance 5 ASA of whom 86% had appropriate renal function monitoring. 27% CD were on 5 ASA of whom only 58% had renal function checked in the past year. 7% UC and 9% CD had prolonged steroid courses prescribed. 9% and 7% of UC and CD had repeated courses of steroids in the previous year. AZA use was equivalent in the two groups ( 20%). However, appropriate blood monitoring was significantly different between UC and CD (93% UC vs 10% CD, p = 0.001). The number of patients on AZA who were offered Pneumoccocal vaccination (UC 50% vs CD 60%) and Influenza vaccination (UC 57% vs CD 20%) was considerably short of the audit standards. Conclusion: This audit identifies areas of IBD practice in primary care that are performed to a high standard, namely the monitoring of blood tests in patients with UC, and the low use of steroids in both groups. There remain areas that require improvement, notably the vaccination status of patients on AZA, and the inappropriate prescribing of 5 ASA in CD. The findings should prompt improved networking between primary and secondary care, a role which could be fulfilled by an IBD specialist nurse. References: 1 UK IBD audit steering group . IBD audit round three. RCP 2012. 2 Mowat C, et al . Guidelines for the management of IBD in adults. Gut 2011 May;60 (5). 3 Rahier JF, et al . Second European evidence-based consensus on the prevention, diagnosis and management of opportunistic infections in IBD. J Crohns Colitis . 2014 Jun;8 (6). Disclosure of Interest: None Declared